Aktivitas Antioksidan Yoghurt Sinbiotik Berbasis Daging Kelapa Muda (Cocos nucifera L.) dan Ubi Jalar Ungu (Ipomoea batatas L) - Winie Vania Tasya Siswandi; Gregoria Sri Suhartati Djarkasi; Maya M. Ludong; Thelma D. J. Tuju; Mercy I. R. Taroreh; Erny J. N. Nurali (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
Synbiotic yogurt is a semi-thick liquid drink containing prebiotics and probiotics. The research objectives were to analyze the physical and chemical properties, measure antioxidant activity, and determine the level of preference for color, taste, aroma, and texture of synbiotic yogurt based on young coconut meat and purple sweet potato. The method used was a completely randomized design (CRD) with the addition of purple sweet potato pulp (0%, 5%, 10%, 15%, 20%, 25%). The results of the research on synbiotic yogurt based on young coconut meat and purple sweet potato have an average viscosity of 10,27 cP-10,90 cP, pH 3,86 – 4,01, total dissolved solids 7,83°Brix-8,17°Brix, total acid 0,84%-0,98%, color 4,47-5,93 (neutral-like very much), taste 4,30-5,00 (neutral-like), aroma 4,70-5,33 (like) and texture 4,63-5,47 (like) and antioxidant activity in treatment P5 (25% purple sweet potato pulp) percent inhibition 86,88% and IC50 80,73 ppm (strong).